A silicon-on-insulator slab for topological valley transport - He, Xin-Tao; Liang, En-Tao; Yuan, Jia-Jun; Qiu, Hao-Yang; Chen, Xiao-Dong; Zhao, Fu-Li; Dong, Jian-Wen (Nature communications, 2019)
Backscattering suppression in silicon-on-insulator (SOI) is one of the central issues to reduce energy loss and signal distortion, enabling for capability improvement of modern information processing systems. Valley physics provides an intriguing way for robust information transfer and unidirectional coupling in topological nanophotonics. Here we realize topological transport in a SOI valley photonic crystal slab. Localized Berry curvature near zone corners guarantees the existence of valley-dependent edge states below light cone, maintaining in-plane robustness and light confinement simultaneously. Topologically robust transport at telecommunication is observed along two sharp-bend interfaces in subwavelength scale, showing flat-top high transmission of ~10% bandwidth. Topological photonic routing is achieved in a bearded-stack interface, due to unidirectional excitation of valley-chirality-locked edge state from the phase vortex of a nanoscale microdisk. These findings show the prototype of robustly integrated devices, and open a new door towards the observation of non-trivial states even in non-Hermitian systems. Backscattering is one of the major factors that limit the performance of integrated nanophotonics. Here, He et al. realize topologically protected, robust and unidirectional coupling as well as optical transport on a silicon-on-insulator platform by exploiting the valley degree of freedom.